Technological Pedagogical Strategies in the Improvement of Basic Functions and Management of Mathematical Operations - Núñez-Naranjo, Aracelly Fernanda; Mora-Rosales, José (Journal of Ecohumanism, 2024)
This study aimed to analyze the contribution of techno-pedagogical strategies in strengthening mastery in mathematical multiplication with students at the basic elementary level in Ecuador. The post-positivist paradigm, quantitative approach, quasi-experimental and comparative design was used, with pre-test and post-test to 4 groups (A, N, B and G) of 30 students each. The first A was the control and the remaining three N, B and G, the experimental ones. During the pre-test, the groups received training through demonstration strategies in the classroom, exercises and teamwork, evaluated with a knowledge test of ten exercises with true and false options. The following week (post-test), group A received reinforcement with the same strategies, while the others received it simultaneously in separate classrooms, with different teachers, using technological strategies based on the tools Nearpod, Blooket and Genially, to be evaluated again using the same strategy. The results indicate that for group A, there were no significant differences between the median scores (p ≥ 0.05) while, in the remaining groups, a significant improvement was observed (p = 0.000), where group B, using the Blooket resource, reflected a greater increase in the median score. It is concluded that these resources can be integrated as pedagogical strategies and significantly favor the mastery of the basic mathematical function in multiplication and specifically with the use of Blooket, highlighting the importance of technological innovation in educational training.